2016
DOI: 10.1590/1678-4162-8580
|View full text |Cite
|
Sign up to set email alerts
|

Prebiótico, probiótico e simbiótico para larvas de Trichogaster leeri (Bleeker, 1852, Perciformes, Osphronemidae)

Abstract: Prebiótico, probiótico e simbiótico para larvas de Trichogaster leeri (Bleeker, 1852, Perciformes, Osphronemidae) [Prebiotic, probiotic and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
1
5
0
4
Order By: Relevance
“…Similar results have been reported for aquatic species fed MOS (Gültepe, Salnur, Hoşsu, & Hisar, 2011;Refstie, Baeverfjord, Seim, & Elvebø, 2010;Staykov, Spring, Denev, & Sweetman, 2007), BS (Essa et al, 2010;Giri et al, 2014) and MOS plus BS as synbiotic (Azevedo et al, 2016;Daniels, Merrifield, Ringø, & Davies, 2013) The mechanisms by which prebiotics and probiotics can improve the performance are still unclear. However, Bacillus sp.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Similar results have been reported for aquatic species fed MOS (Gültepe, Salnur, Hoşsu, & Hisar, 2011;Refstie, Baeverfjord, Seim, & Elvebø, 2010;Staykov, Spring, Denev, & Sweetman, 2007), BS (Essa et al, 2010;Giri et al, 2014) and MOS plus BS as synbiotic (Azevedo et al, 2016;Daniels, Merrifield, Ringø, & Davies, 2013) The mechanisms by which prebiotics and probiotics can improve the performance are still unclear. However, Bacillus sp.…”
Section: Resultssupporting
confidence: 79%
“…In aquaculture, this prebiotic demonstrates to improve the growth performance, survival, feed utilization, non-specific immunity and disease resistance (Burr, Hume, Ricke, Nisbet, & Gatlin III, 2008;Liu et al, 2013;Safari, Shahsavani, Paolucci, & Atash, 2014). Among the probiotics commonly used, the genus Bacillus is one of the most extensively evaluated as aquaculture feed supplements and has been demonstrated to improve a number of attributes when supplemented in diets of aquatic organisms (Azevedo, Fosse Filho, Pereira, Andrade, & Júnior, 2016;Geng et al, 2012;Ghosh, Sinha, & Sahu, 2008;Giri, Sukumaran, Sen, & Jena, 2014;Gupta, Gupta, & Dhawan, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it has been reported that juvenile large yellow croaker Larimichthys crocea fed B. subtilis (1.35 × 10 7 CFU/g) and fructooligosaccharide (4 g/kg) had higher WG and SGR compared with the control group (Ai et al, ). Moreover, one research group fed pearl Gourami Trichopodus leerii with B. subtilis Cohn (2 g/kg diet) and mannan oligosaccharide (2 g/kg diet) and reported a higher SGR compared with the control group (Azevedo, Fosse Filho, Pereira, Andrade, & Júnior, ). Generally, major mechanisms of probiotic action include enhancement of epithelial barrier, competitive exclusion of pathogenic microorganisms and production of antimicrobial substances, resulting in improved digestion and host growth (reviewed in (Bermudez‐Brito, Plaza‐Díaz, Muñoz‐Quezada, Gómez‐Llorente, & Gil, ; Ringø et al, )).…”
Section: Discussionmentioning
confidence: 99%
“…Entre as inovações no setor da nutrição de peixes ornamentais estão os aditivos alimentares, como as enzimas exógenas (GOMES et al, 2018), prebióticos (ABASALI e MOHAMAD, 2011), probióticos (FIROUZBAKHSH et al, 2011) e simbióticos (AZEVEDO et al, 2016), que tem demostrado resultados positivos sobre o desempenho e imunidade dos peixes.…”
Section: Introductionunclassified